Working-class Raj: colonialism and the making of class in British India - Lindgren-Gibson, Alexandra 1982- (Cambridge, UK; New York, USA: Cambridge University Press, 2024)
"Working-Class Raj explores what happened to working-class men and women when they left Britain and travelled to India, where their worlds were upended by the disruptive addition of race to British social hierarchies. Drawing on previously unused correspondence collections, this book puts British workingclass history in a global perspective"--
Family histories and remaking class in British India -- Writing family together across imperial distances -- Military domesticity: creating working-class worlds in British India -- Servants in empire: wives, daughters, and domestic service -- Class and colonial knowledge: miseducation for empire -- Fragmented families: tracing the afterlives of working-class India.
Includes bibliographical references and index.
Keywords: Working class -- India -- History; Sociology; English -- India -- History; Emigration and immigration -- India -- History; Families -- India -- History; Great Britain -- Colonies